2020
DOI: 10.1016/j.jfranklin.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Robust control for vibration control systems with dead-zone band and time delay under severe disturbance using adaptive fuzzy neural network

Abstract: This study proposes a novel adaptive control method to deal with the dead-zone and time delay issues in actuators of vibration control systems. The controller is formulated based on a type-2 fuzzy neural network integrating with a new modification of Riccati-like equation. The developed new type Riccati-like equation is significant as it reduces energy consumption of control inputs to minimum. Two approaches are suggested to improve performance of the system using the basic elements of Riccati equation. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…They found that it had better motion than a flexible manipulator with no time delay. Phu D X et al [33][34][35][36], to improve the comfort of car seats, proposed a new control strategy to improve ride comfort and applied it to the vibration control of automobile seat suspension with MR damper. The experimental results show the effectiveness of the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…They found that it had better motion than a flexible manipulator with no time delay. Phu D X et al [33][34][35][36], to improve the comfort of car seats, proposed a new control strategy to improve ride comfort and applied it to the vibration control of automobile seat suspension with MR damper. The experimental results show the effectiveness of the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars have conducted a lot of studies to improve vehicle ride comfort [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Qi et al [8] proposed a new type of suspension including a hydraulically interlinked suspension and electronically controlled air springs, enabling a high level of performance in terms of both handling stability and ride comfort.…”
Section: Introductionmentioning
confidence: 99%
“…e results show that the controller can control the acceleration and displacement at the driver position effectively. Phu et al [20] proposed a novel adaptive control method to deal with the dead zone and time delay issues in actuators of vibration control systems. e unwanted vibrations due to external excitations are well controlled despite of the presence of dead zone and time delay in actuators.…”
Section: Introductionmentioning
confidence: 99%
“…It causes the delay of feedback control force, and then affects the response of suspension system. 23,24 Although the delay time may be short, when it appears in the feedback loop, it can considerably cause control performance deterioration and control system unstable. 25,26 Consequently, the analysis of time delay control has a highlighted research topic in the past few years.…”
Section: Introductionmentioning
confidence: 99%